Eric Seiferth. - SEIFERTH, ERIC (Historic New Orleans Collection Quarterly)
The article profiles Eric Seiferth, an associate curator and historian, who works with the technology department to create virtual exhibitions for The Historic New Orleans Collection's (THNOC). Topics discussed include the advantages of virtual exhibitions, including an increased accessibility and longevity of the show, and information on some virtual exhibitions that Seiferth helped create.